2009
DOI: 10.1097/jsm.0b013e3181b8c136
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Female Athlete Triad in High School Athletes and Sedentary Students

Abstract: Objective To determine the prevalence of the female athlete triad (low energy availability, menstrual dysfunction and low bone mineral density) in high school varsity athletes in a variety of sports compared with sedentary students/controls. Design Prospective study. Setting Academic medical center in the Midwest. Participants Eighty varsity athletes and eighty sedentary students/controls volunteered for this study. Intervention Subjects completed questionnaires, had their blood drawn and underwent bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
140
8
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(166 citation statements)
references
References 28 publications
12
140
8
6
Order By: Relevance
“…Using a definition of MI similar to ours, Hoch et al lO reported an overall much higher prevalence of MI in the athletic population (54%). 10 The difference in their findings compared with ours and those of other studies l3 ,14 cannot be explained. Interestingly, Hoch et al lO reported the prevalence of MI in their sedentary control population as 21 %, which is similar to that in our population of female athletes and in other studies of female athletes.…”
Section: Discussioncontrasting
confidence: 56%
“…Using a definition of MI similar to ours, Hoch et al lO reported an overall much higher prevalence of MI in the athletic population (54%). 10 The difference in their findings compared with ours and those of other studies l3 ,14 cannot be explained. Interestingly, Hoch et al lO reported the prevalence of MI in their sedentary control population as 21 %, which is similar to that in our population of female athletes and in other studies of female athletes.…”
Section: Discussioncontrasting
confidence: 56%
“…Por outro lado, a literatura aponta que a insatisfação corporal acomete tanto as atletas quanto as não atletas (Hoch et al, 2009;Reiking & Alexander, 2005). Rosendahl et al (2009) explicam que as atletas são expostas às mesmas mensagens socioculturais direcionadas para a magreza que as não atletas.…”
Section: Discussionunclassified
“…Furthermore, 39% of athletes and 36% of controls had an EA <45 kcal/ kg FFM per day. 9 Disordered eating in adolescent athletes has been evaluated by using a variety of survey tools, such as the Eating Disorder Exam Questionnaire, the Eating Disorder Inventory, and the Three-Factor Eating Questionnaire. Studies that used these tools provide estimates of disordered eating ranging from 0% to 54%.…”
Section: Risk Factorsmentioning
confidence: 99%
“…7,8 It is difficult to estimate the true prevalence of the triad because of the complexity of evaluation of each of the components. Reports have indicated that the prevalence of individuals with all 3 components simultaneously is only 1% to 1.2% in high school girls 9,10 and 0% to 16% in all female athletes. In high schoolaged female athletes, the prevalence of 2 concurrent components of the triad is 4% to 18% and of any 1 component is as high as 16% to 54%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation